Algorithmic Aspects in Information and Management 6th International Conference, AAIM 2010, Weihai, China, July 19-21, 2010. Proceedings - Chen, Bo.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This volume constitutes the proceedings of the International Conference on Algorithmic Aspects in Information and Management, AAIM 2010, held in Weihai, China, in July 2010.
Comparison of Two Algorithms for Computing Page Importance -- The Invisible Hand for Risk Averse Investment in Electricity Generation -- Efficient Algorithms for the Prize Collecting Steiner Tree Problems with Interval Data -- The (K,k)-Capacitated Spanning Tree Problem -- Optimal Algorithms for the Economic Lot-Sizing Problem with Multi-supplier -- Synthetic Road Networks -- Computing Exact and Approximate Nash Equilibria in 2-Player Games -- Where Would Refinancing Preferences Go? -- Approximating Maximum Edge 2-Coloring in Simple Graphs -- A Linear Kernel for Co-Path/Cycle Packing -- A VaR Algorithm for Warrants Portfolio -- Some Results on Incremental Vertex Cover Problem -- Finding Good Tours for Huge Euclidean TSP Instances by Iterative Backbone Contraction -- Point Location in the Continuous-Time Moving Network -- Coordinated Scheduling of Production and Delivery with Production Window and Delivery Capacity Constraints -- Inverse 1-median Problem on Trees under Weighted l ??? Norm -- On the Approximability of the Vertex Cover and Related Problems -- Feasibility Testing for Dial-a-Ride Problems -- Indexing Similar DNA Sequences -- Online Scheduling on Two Uniform Machines to Minimize the Makespan with a Periodic Availability Constraint -- A New Smoothing Newton Method for Symmetric Cone Complementarity Problems -- Approximation Algorithms for Scheduling with a Variable Machine Maintenance -- Bounded Parallel-Batch Scheduling on Unrelated Parallel Machines -- Exact Algorithms for Coloring Graphs While Avoiding Monochromatic Cycles -- Randomized Approaches for Nearest Neighbor Search in Metric Space When Computing the Pairwise Distance Is Extremely Expensive -- A Primal-Dual Approximation Algorithm for the k-Level Stochastic Facility Location Problem -- Optimal Semi-online Scheduling Algorithms on Two Parallel Identical Machines under a Grade of Service Provision -- Varieties of Regularities in Weighted Sequences -- Online Uniformly Inserting Points on Grid -- Kernelization for Cycle Transversal Problems -- Online Splitting Interval Scheduling on m Identical Machines -- Extended Tabu Search on Fuzzy Traveling Salesman Problem in Multi-criteria Analysis -- Efficient Exact and Approximate Algorithms for the Complement of Maximal Strip Recovery.
Keywords: Computer science; Data structures (Computer science).; Computer software; Computational complexity; Artificial intelligence; Information Systems; Computer Science; Algorithm Analysis and Problem Complexity; Discrete Mathematics in Computer Science; Management of Computing and Information Systems; Data Structures; Artificial Intelligence (incl. Robotics).; Mathematics of Computing